The Mirror Exercise and the Restructuring of the Parent-Child Relational Unit. (2nd October 2018) - Lee, Adrienne
Abstract: This article presents the mirror exercise as a method of updating, restructuring, and enlivening Parent-Child relational units. The exercise method is presented with a commentary and case illustration. The author puts the process in the context of Parent ego state introjection theory and treatment and the self-reparenting work of Muriel James as well as integrating Adult ego state theory. She emphasizes the importance of relationship as a therapeutic method, not specifically between the therapist and the client but as an intrapsychic experience of internal relating. The role and significance of the observing self or metaperspective in monitoring the experience and enabling Adult integration are also explored.